Revolutionizing Digital Banking: Bridging Generational Gaps to Deliver Exceptional Customer Loyalty - Ignatius Hari Santoso; Maryono Maryono; Ali Maskur; Sri Nawatmi; Mulyo Budi Setiawan (Telaah Bisnis, 2025)
This study investigate how omnichannel integration quality comprised of channel consistency, channel transparency and channel connectivity shape the online customer experience and its subsequent influence the willingness to stay in digital banking. Drawing upon the Stimulus – Organism – Response framework, the research also examined whether the generational cohorts moderate these relationship. A quantitative method with purposive sampling is employed, involving 90 valid response from Indonesian digital banking users, belonging to Generation Y and Z. Structural equation modelling using Smart PLS is applied to assess. The findings reveal that channel connectivity does not exert a meaningful effect. Furthermore, online customer experience strongly predicts the customers’ willingness to stay. These result suggest that consistency and transparency remain critical lever for optimizing digital experiences, while connectivity has become baseline expectation rather than a differentiating factor. This research extends the online customer experience and omnichannel literature by highlighting generational convergence in digital expectation. Practically it advises banks to prioritize the seamless, transparent and consistent service delivery to strengthen customer retention.